Knowledge, attitude, and behaviour around concussion at the FIFA Women`s World Cup 2023: part 1 - medical staff - Wilke, C. F.; Serner, A.; Massey, A.; McCall, A.; Fulcher, M.; Rosenbloom, C.; Carmody, S.; Patterson, S. D.; Okholm Kryger, K. (Science and Medicine in Football, 2025)
The objective of this observational cross-sectional study was to assess the knowledge, attitudes and behaviours of medical staff participating in the FIFA Women`s World Cup 2023 regarding the assessment and management of concussion in football. Medical staff from 32 teams qualified for the FIFA Women`s World Cup 2023 were invited to answer an online survey. Results were analysed descriptively. 47 participants completed the survey. Concussion knowledge: 98% were aware of concussion protocol(s). Most concussive signs or symptoms were recognised, though only 36% of participants (n = 17) correctly reported potential symptom onset time. Knowledge on assessment and return to play elements varied. Attitude: 77% (n = 36) reported being very confident or confident in recognizing a suspected concussion. When assessing a suspected concussion on the pitch, 55% (n = 26) reported to have felt pressured by the player sometimes, very often or always, and 47% (n = 22) by the coaching staff. Behaviour: Among doctors, 70% reported their national team performs baseline concussion assessments. Reported use of on-field assessment elements suggested in concussion guidelines varied between 5% and 95%. In conclusion, most medical staff participating in the FIFA Women`s World Cup 2023 were generally knowledgeable about concussion, reported on-pitch and return to play attitudes and behaviours aligning with evidence-based standards for safeguarding players` health. However, gaps were observed in all three domains, compared to guidelines. Expanding education to players and coaching staff is suggested to facilitate the delivery of evidence-based best practice.